Management of Existing Cyber Legal Problems: Prevention and Control: Addressing Privacy and Freedom Concerns in Cyber Legal Problems (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The development in the field of Information and Communication Technology (ICT) shows the various patterns and difficulties in cyber law. Based on development of jurisprudence and rising patterns, it can be invoked that some expansive cyber law patterns are probably going to rise. Cyber world is both informational and interactive with heaps of self-governance. As everything is accessible on internet which people improve the situation their own comfort including individual subtle elements, proficient points of interest, bank subtle elements, and even private keys of people. All these information can prompt a serious privacy risk. Alongside that how much private information of an individual ought to be open to government. Likewise, Hate discourse on internet, or discourse designed to target, mistreat or instigate scorn or savagery against a man or gathering in view of cast, creed, race, religion, nationality, gender, sexual orientation, disability or other gathering characteristic, don't get affected by areas, time and limits. Because of the openly accessible internet services worldwide, occurrences of disrespect talk has turned out to be known all through the world inside seconds and can cause serious repercussion. India by and by does not have a particular legislation representing information assurance or privacy particularly in IT law. Be that as it may, according to Article-21 which offers right to privacy and Section-19A which manages opportunity of articulation under The Constitution of Indian yet at the same time there working isn't actively included when it goes under cybercrime. Despite the fact that India has thought of IT Act, 2000 and the resulting amendment to it in 2008 yet it can't cover the entire limits of cybercrimes, similar to an exceptionally essential issue of right to privacy. This exclusive demonstrates the irregularity between age old technique received in India and the progression which Indian culture has made. The session centers around the progression of cyber world with deference of privacy concerns and flexibility issues with extraordinary reference to cyber laws of nations like India, European Nations and United States of America. The issue of how to accommodate all the clashing cases emerging out of the issues of privacy with regards to Internet introduction and the right to the right to speak freely.